Expression and persistence of a lacZ reporter gene at various stages of tilapia (Oreochromis niloticus) - Alam, M D Samsul; Maclean, Norman (Indian Journal of Fisheries, 2011)
An Escherichia coli lacZ gene linked to the 4.6 kb carp ~-actin promoter/enhancer was microinjected into the fertilised eggs of til apia COreochromisniloticus) at a concentration of 5xl05 copies per egg. The embryos grown fromthe injected eggs were homogenised at day 8 and day 14 after fertilization andhalf of the homogenate was used for assaying ~-galactosidase activity by afluorometric method using 4-methyl-umbelliferyl ~ D Galactoside as asubstrate. DNA from the other half of the homogenate was analysed bySouthern Blotting. The incidence of expression of the trans gene was 41.6 and25.0% for the 8-days old embryo and 14 days old fry respectively. All theexpressing individuals were positive for carrying the transgene in differentconcatemeric forms. Out of eight tissues analysed from a six-month old adultfish by X-Gal staining, only certain cells of the brain were found to be positivefor express.on of the lacZ gene although the DNA was present in all the tissueswhen anal:{sed by Southern Blotting.